2002
DOI: 10.1038/sj.bjp.0704481
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the non‐nitrergic NANC relaxation responses in the rabbit vaginal wall

Abstract: 1 Electrical ®eld stimulation (EFS)-induced non-adrenergic non-cholinergic (NANC) relaxation responses in the rabbit vaginal wall were investigated. 2 These NANC responses were partially inhibited with the nitric oxide synthase (NOS) inhibitors N G -nitro-L-arginine methyl ester (L-NAME; 500 mM), N G -nitro-L-arginine (300 mM) or N-iminoethyl-L-ornithine (500 mM) or the selective soluble guanylate cyclase inhibitor 1H-[1,2,4]oxadiazolo[4,3,-a]quinoxalin-1-one (ODQ, 10 mM). Application of L-NAME and ODQ concomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
49
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 29 publications
6
49
0
Order By: Relevance
“…5,6 In the latter tissue, an additional unidentified neurotransmitter is also involved. 7 The results of the present study support the hypothesis that NO/cGMP plays a significant role in the regulation of vaginal and clitoral blood flow changes in response to neurogenic stimulation in 19 to potentiate neurogenic relaxation of rabbit clitoral smooth muscle 5,6 and to potentiate the increase of rabbit genital blood flow in response to pelvic nerve stimulation. 20 In this study, vardenafil was able to potentiate the vascular sexual response in clitoris and vagina 20 min after intravenous administration, with the effect lasting at least 80 min afterwards, raising the possibility of a wide therapeutic window.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…5,6 In the latter tissue, an additional unidentified neurotransmitter is also involved. 7 The results of the present study support the hypothesis that NO/cGMP plays a significant role in the regulation of vaginal and clitoral blood flow changes in response to neurogenic stimulation in 19 to potentiate neurogenic relaxation of rabbit clitoral smooth muscle 5,6 and to potentiate the increase of rabbit genital blood flow in response to pelvic nerve stimulation. 20 In this study, vardenafil was able to potentiate the vascular sexual response in clitoris and vagina 20 min after intravenous administration, with the effect lasting at least 80 min afterwards, raising the possibility of a wide therapeutic window.…”
Section: Discussionsupporting
confidence: 78%
“…[2][3][4] Although the neurogenic control of the vascular events in these tissues has not been thoroughly investigated, it is known that the nitric oxide (NO)/cGMP pathway mediates the neurogenic relaxation of rabbit clitoral corpus cavernosum and is involved in the neurogenic relaxation of rabbit vagina. [5][6][7] Vardenafil is a potent and selective type 5 phosphodiesterase (PDE5) inhibitor that enhances NO-mediated relaxation of human corpus cavernosum and NO-induced rabbit penile erection, and it has been reported to potentiate erectile function in patients. 8,9 Furthermore, vardenafil is currently under clinical investigation for the treatment of erectile dysfunction (ED).…”
Section: Introductionmentioning
confidence: 99%
“…Vagina P2X5 and P2X7 r eceptors have been l ocal ised immunohistochemically in the stratified squamous epithelium of rat vagina, and it was suggested that they play a role in the physiological turnover of continuously regenerating cells [28,156]. Adenosine A 2A and P2 receptors are present in the wall of the rabbit vagina that mediate relaxation, but it was suggested that they are not involved in the NANC relaxant responses that remained after removal of NO transmission by the NOS inhibitor, L -NAME [459,460]. P2Y 2 receptor-selective agonists stimulate vaginal moisture in ovariectomised rabbits and P2Y 2 receptor mRNA is localised in stratified squamous epithelium of the vagina [276].…”
Section: Placentamentioning
confidence: 99%
“…However, in the rabbit vagina NO mediates only 25-30% of the NANC relaxation response, the remaining majority seems to be mediated by a yet unknown neurotransmitter. 12,13 Further studies with human vagina will be required to verify the functional existence of this elusive transmitter. …”
Section: Discussionmentioning
confidence: 99%